Approbatoin of the marketing method of conjoint analysis on the example of contraceptives - Mahanova, T. V.; Tkachenko, N. O.; Маганова, Тамара Валеріївна; Ткаченко, Наталя Олександрівна (Харків : НФаУ, 2021)
Improving the methods of strategic management of any system is crucial for the growth of functional efficiency and is inextricably linked with its marketing activities, especially with its analytical aspect. The most important thing for analytical marketing is the study of the characteristics of the consumer, who shows his needs to the system. Therefore, consumer research is relevant, considering drug supply systems in the prism of patient-oriented treatment and prevention.